Assessment of genetic polymorphism associated with ATP-binding cassette transporter A1 (ABCA1) gene and fluctuations in serum lipid profile levels in patients with coronary artery disease - Neda M. Bogari; Ahmad O. Babalghith; Abdellatif Bouazzaoui; Ashwag Aljohani; Anas Dannoun; Osama Elkhateeb; Amr A. Amin; Mazin K. Bogari; Abdulbari A. Mazhar; Massimo Porqueddu; Imran Ali Khan (Elsevier, 2021)
Background: Coronary artery disease (CAD) is one of the common genetic and clinical risk factors associated with cardiovascular and multifactorial disorder. ATP-binding cassette transporter A1 (ABCA1) gene plays an important role in lipid metabolism and in multiple studies associated with CAD. However, more studies are needed to identify the exact role of single nucleotide polymorphisms which may cause CAD. Objectives: The aim of this study is to investigate the genetic association of polymorphism g.1051G > A in the ABCA1 gene with CAD patients in the Saudi population. Methods: We included 315 confirmed CAD cases, and 205 non-CAD or control subjects in this case-control study. DNA isolation was carried out for all registered participants and the polymorphism g.1051G > A was genotyped with Polymerase Chain Reaction followed by Restriction Fragment Length Polymorphism analysis with EcoNI restriction enzyme. Results: Modifiable risk factors such as Body Mass Index, smoking and diabetes were strongly associated and non-modifiable risk factors such as hypertension (Systolic Blood Pressure and Diastolic Blood Pressure) and serum analysis such as Fasting Blood Glucose, Total cholesterol (TC), Triglyceride (TG) and LDL-c were significantly associated in CAD cases (p < 0.05). Allele (OR-1.73;95% CI:1.33-2.26; p = 0.0004), GA vs GG (OR-2.26; 95% CI: 1.53-3.35; p = 0.0003 and dominant inheritance pattern (OR-2.23; 95% CI:1.56-3.20; p = 0.00009 was strongly associated with CAD cases and control subjects. The frequency level of use of atorvastatin was significantly different among GG, GA and AA subjects. Additionally, TC and TG levels were influenced by the presence of g.1051G > A polymorphism. Conclusion: The polymorphism g.1051G > A in the gene ABCA1 is closely associated with the existence of the CAD subjects. This polymorphism could also affect the serum levels of the lipid profile, suggesting a possible occurrence of CAD in the Saudi population.